PERSEPSI MASYARAKAT TERHADAP KUALITAS PELAYANAN e-KTP DI KECAMATAN GONDOKUSUMAN KOTA YOGYAKARTA - , Imelda Beatriz Imbab, SE ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Kecamatan Gondokusuman Kota Yogyakarta is one of regions becoming pilot project of e-KTP implementation nationally. e-KTP is a program of the administration of Republic of Indonesia, mainly the Ministry of Internal Affairs as the instruction of UU No. 23 Tahun 2006 on Population Administration. e-KTP is a follow-up or improvement of KTP. In the past, it is usually heard that service and processes of KTP making were complicated, took very long time, expensive, and hard. Everyone had to pass bureaucracy lines beginning from RT/RW till district just to get an ID. This fact shows a strong indication on bad social perception on the service quality of e-KTP. Legal products and bureaucracy reform regarding the service of e-KTP making instruct several changes like short time, free, and simple. It is strongy assumed this will cause a shift or change of social perception on the quality of e-KTP making. In or der to understand to what extent social perception on the quality of e-KTP making, this thesis is urgently and important to be done. This research used description method qualitatively and quantitatively. Data were collected normally by considering data normality. Primary data were obtained through observation, interview, and questioner. Secondary ones were obtained through literature and documentation studies. Informants and respondents were determined with purposive sampling method. Research object was Gondokusuman District office. Research subjects were Gondokusuman people who got e-KTP service. Data validity was done with triangulation. I used sources and theories triangulation, by using a number of data sources and theories to collect information similarity. Data anaysis technique used inductive. This thesis aimed at understanding social perception on the quality of e-KTP service in Gondokusuman District. There are ten indicators to understand social perception on the quality of e-KTP service in Gondokusuman District. The ten indicators include service time, service accuracy, officers politeness and hospitality, officers responsibility, the availability of e-KTP making facilities, the easiness to get e-KTP service, model variation of service, personal service, comfortness in getting service, and supporting attributes of service. Research results showed that: (1) the quality of e-KTP service in Gondokusuman District is not satisfying yet, (2) eight indicators (service time, service accuracy, officers poiteness and hospitality, officers rersponsibility, service availability, easiness to get service, comfortness in getting service, and supporting attributes of service) strengthen social perception on the quality of e- KTP service in Gondokusuman District, and (3) two indicators (model variation of service and personal service) discourage social perception on the quality of e- KTP service in Gondokusuman District. Further, the quality of e-KTP service in Gondokusuman District still has to be improved mainly regarding functions and promises following the implementation of e-KTP such as online and banking transactions.